The Elderly Promote and Potential Development in Chiangrai Province - Matanboon, Wichulada; Deemoh, Bundit; Sairorkham, Banjit (Interdisciplinary Academic and Research Journal, 2023)
The elderly population is regarded as a person with potential, knowledge, ability, and life experience. Therefore, they should be encouraged and developed their potential to bring out the existing potential to help their communities and society development in addition, Thai society has become a fully aging society and then came to this research article. This research article aimed to promote potential development in Chiangrai elderly. The research area focused on Chiangrai Province, collecting data through in-depth interviews with 6 provincial elderly leaders, group interview 1 group (8 persons) of provincial elderly leaders, and a workshop with 80 district elderly leaders from 18 districts in Chiangrai Province and lead to the grouping promoted and potential development in elderly for community development activities. The research found 1)Chiangrai elderly had participatory potential in community development, participatory occupation, wisdom part had a strong elderly working network and work continually by working integrated with other elderly issues.2)This project developed elderly potential in Chiangrai province by participatory community development 20 elders and developed network district elderly leader in 19 districts (190 persons) lead to working mechanism in committee pattern for coordinate mechanism between district and provincial level, elderly data sharing in needs and situation once per month.